Perception about Student Engagement in Blended Learning Instructional Design: Evidence from Sri Lankan Universities - Jayarathna, N. G. D. A.; Herath, H. M. M. N. (ASEAN Journal of Educational Research and Technology, 2024)
The main purpose of this study was to evaluate students’ perceptions of blended learning instructional design in universities in Sri Lanka. The COVID-19 pandemic has created challenges and disrupted the Higher Education sector; university campuses closed, and face-to-face teaching and assessment shifted to an online format. Currently, most universities are offering their degrees using blended learning instructional mode, and due to that students’ feedback will be very important. The study was conducted for state universities in Sri Lanka and a structured questionnaire was distributed among students. The study's findings showed that students have a favorable opinion of blended learning programs. It is stated that students’ perception of the preferred mode of learning, the impact of blended learning, the effectiveness of different blended learning tools, satisfaction regarding different components of blended learning, and finally overall satisfaction with the blended learning approach. The blended learning course appeared to have positive effects on student engagement, learner autonomy, linkage of learning to real-world situations, and flexibility.